(untitled) (Sciences & Technologie. B, Sciences de l’ingénieur, 2001)
A finite element package PAFEC was used to analyse both an internal panel of a uniformly loaded slab continuous over a rectangular grid of beams simply supported at their intersections, and a similar but single panel for various aspect ratios and various adjacent beam stiffness relationships. The object has been to determine values of the adjacent beam/slab stiffness ratios (g1-g2) for which the distribution of the bending moments across the slabs in the two orthogonal directions is uniform, as is the load distribution on the supporting beams. These particular cases of structural behaviour, identified as the twistless cases, could be exploited for developing an alternative design procedure for slab-beam systems. Several small scale slab-beam models with twistless beam/slab ratios have been tested to determine their behaviour under the action of a uniformly distributed load. The test results are presented and compared to the theoretical values.